Your life calling : reimagining the rest of your life - Pauley, Jane, 1950- (New York : Simon & Schuster, 2014)
"In this inspirational book, beloved broadcast journalist Jane Pauley helps people over fifty successfully navigate the 'reinvention' phase of their lives and build a positive, powerful future"--
Moment of impact -- Out of the blue -- The holy grail -- Something more -- Do-overs -- Changes -- Daughter of a musician -- The gift -- The next act -- Finding balance -- In alignment -- Packing for a long trip -- "And she landed on her feet" -- Up periscope -- Less think, more do -- Inspiration is everywhere -- Work you want to do -- The mother of reinvention -- Epiphanies happen -- One step at a time -- Spirit of adventure -- Do something different -- Two degrees of cooperation -- Back to school -- The call of the wild -- Reality checks -- Talk therapy -- Just say yes -- Commencement.
Keywords: Pauley, Jane, -- 1950-; Career changes -- Case studies; Change (Psychology); Self-realization.; Middle-aged persons -- Psychology